PHYTOCHEMICAL SCREENING, ANTIOXIDANT ASSAY OF JUNIPERUS RECURVA AND STUDY OF IT’S IN VITRO CYTOTOXICITY AGAINST BREAST CANCER CELL LINES - JAYA BHANDARI; ASMA NAQVI; PRASODHAN NIRAULA; PRATIKSHYA THAPA; NITA THAPA; NIKITA SHRESTHA; BHUPAL GOVINDA SHRESTHA (International Journal of Pharma and Bio Sciences, 2015)
Over 70% of anticancer drug has their origin as natural products and only a small part of the massive reservoir of the bioactive components on Earth has been studied. This study comprises the phytochemical screening, antimicrobial tests, antioxidant (DPPH) assay, and in-vitro cytotoxicity against MCF-7 (Breast cancer) cell lines of different plant-parts of Nepalese medicinal plant Juniperus recurva.This is the first study of the effects of Juniperus recurva against the breast cancer (MCF-7) cell lines. Two different extracts of leaves of two different parts of the tree of J. recurva (JRL1 and JRL2) and two extracts of seeds of J. recurve JRSO(Outer coat of seed) and JRSib (Inner black seed without the coat) were taken for studies. The zones of inhibitionin the antimicrobial tests of the extracts of a leaf extract (200mg/mL) against B. cereus, B. thuringiensis, E. coli, P. aeruginosa, B. subtilis and P. mirabilis were17mm, 15mm, 10mm, 10mm, 15mm and 12 mm respectively and of seed extract (200mg/mL) were 11mm, 10mm, 12 mm, 16mm, 15mm 13mm for seeds respectively and in the same sequence against different microorganisms. The percentage of DPPH scavenging activity is found to increase with the increase in concentration. The highest percent DPPH scavenging activity is found at the maximum concentration used i.e. 10 mg/mL corresponding to the value of 89.25%, 45.01%, 25.74%, 75.09% and 32.81% of ascorbic acid for JRL1(Leaf extract), JRL2 (Leaf extract), JRSib (Seed extract) and JRSO (Seed extract) respectively. MTT assay was carried to determine the IC50 values of different plant-parts extracts. All the plant parts are found to be weakly cytotoxic against MCF-7 with IC50 values of 40.38µg/mL for JRL1 and 50 µg/ml for all other extracts named JRL2, JRSO and JRSib as compared to Standard Doxorubicin i.e. IC50=1.56±0.05µM. Further work on isolation of pure compounds by bioassay guided extraction from the plant J. recurva is suggested so that the higher activity of the pure compounds towards MCF7 and other cancer cell lines can be investigated.